2018
DOI: 10.1016/j.pmedr.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Pilot evaluation of HEAL – A natural experiment to promote obesity prevention behaviors among low-income pregnant women

Abstract: Instituting interventions during the prenatal period is optimal for early obesity prevention in the child. Healthy Eating Active Living (HEAL) is a six-week, multi-component program to promote breastfeeding, healthy dietary habits, cooking skills and physical activity among Medicaid-eligible pregnant-women in Texas. HEAL is integrated into the healthcare system and offered as a standard-of-care for eligible patients. Methods: Preliminary evaluation of this natural experiment conducted from March 2015 through O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…20,31,37,38,41,43,48,52 When CM/CN interventions were provided to the general community, most were delivered by nutrition and/or public health students 26,28,[33][34][35]55 and/or dietitians. 28,40,[49][50][51] Although medical graduates could benefit from the ability to discuss nutrition with their patients 7 and lead coordination of nutrition care with other professionals, particularly dietitians, 56 they report that nutrition education and/or training if provided, is commonly insufficient. 7 The need for better nutrition education for medical practitioners 7,10,12 and other health professionals has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…20,31,37,38,41,43,48,52 When CM/CN interventions were provided to the general community, most were delivered by nutrition and/or public health students 26,28,[33][34][35]55 and/or dietitians. 28,40,[49][50][51] Although medical graduates could benefit from the ability to discuss nutrition with their patients 7 and lead coordination of nutrition care with other professionals, particularly dietitians, 56 they report that nutrition education and/or training if provided, is commonly insufficient. 7 The need for better nutrition education for medical practitioners 7,10,12 and other health professionals has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of culinary nutrition education interventions during preconception, pregnancy, and postpartum, found that the majority (80%) of interventions were “conducted during the postpartum period and targeted nutrition issues in infants and young children”; only 20% of interventions were conducted during pregnancy and none pre-conception [ 14 ]. Cooking programs conducted during pregnancy tend to commence during the second trimester [ 43 , 44 , 45 , 46 , 47 , 48 ]. Participants in our study thought it would be important for an intervention to start earlier in pregnancy; they expressed frustration with lack of early prenatal care and thought that a cooking program could help address first-trimester symptoms such as food aversions, nausea, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The modality and content of existing cooking interventions targeting pregnancy are quite variable, with the majority of cooking programs delivered as one component of a larger lifestyle intervention [ 43 , 44 , 45 , 46 , 47 , 48 ]. Most existing programs have used primarily in-person, hands-on learning in a group setting [ 43 , 44 , 47 , 48 ], some used demonstrations only [ 45 ] (no hands-on component) or one-on-one home visits [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations